Examining the performance of coffee supply chains in Central Vietnam: an exploratory study - Hoang, Dinh Thao Vy (Curtin University, 2017)
This study examines the performance of Vietnam coffee supply chains and the constraints to facilitate a sustainable coffee industry. An exploratory study was conducted in the Central Highlands of Vietnam. The study found that moving down the supply chain, the marketing margin increased to cover the uncertainty of price inherent in highly volatile markets. Farmers failed to meet downstream requirement for quality and quantity. Supply chain members are bonded by trust through enduring long-term relationships.